2012
DOI: 10.1177/147323001204000227
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Concentrations of Inflammatory Cytokines and Chemokines in Patients with Haemorrhagic Fever with Renal Syndrome

Abstract: Serum concentrations of proinflammatory cytokines and chemokines increased in line with disease severity in HFRS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 40 publications
(36 reference statements)
2
31
1
Order By: Relevance
“…In further support of this hypothesis, it has been reported that serum sIL-2R and IL-6 inversely correlate with platelet count and arterial pressure [18]. Additionally, higher serum concentrations of TNF-α, IL-6, IFN-γ, CXCL8 (IL-8) and CCL5 (RANTES) have been observed in the most severe HFRS cases [15,19,20].…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…In further support of this hypothesis, it has been reported that serum sIL-2R and IL-6 inversely correlate with platelet count and arterial pressure [18]. Additionally, higher serum concentrations of TNF-α, IL-6, IFN-γ, CXCL8 (IL-8) and CCL5 (RANTES) have been observed in the most severe HFRS cases [15,19,20].…”
mentioning
confidence: 82%
“…Nevertheless, increased levels of serum proinflammatory cytokines have been observed in HFRS cases at the onset and remain elevated throughout the duration of the disease [15]. Additionally, increased numbers of TNF-α-producing cells have been observed in kidney biopsies of HFRS cases [16].…”
mentioning
confidence: 99%
“…Therefore, it is assumed that capillary leakage is more likely to be caused by redundant cytokines/chemokines and adhesion molecules. Significantly elevated plasma levels of IL-6, IL-8, and CCL5 were detected at the onset of the acute phase of HFRS [12], [54], and higher concentrations were observed in more severe disease types [12]. Increased expression of IL-6 is associated with clinically severe Nephropathia epidemica (NE), and high IL-6 was found to be an independent risk factor for impaired renal function, thrombocytopenia, and longer hospitalization [55].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF), interleukin (IL-6 and IL-10), vascular endothelial growth factor, and cytotoxic T cell-mediated mechanisms are more likely responsible for the symptoms observed in HFRS [7], [8], [9], [10]. Increased levels of TNF, IL-1, IL-6, IL-8, IFN-γ, IP-10, and CCL5 were observed in vivo and in vitro [11], [12], [13], and several cytokines, such as IFN-γ, IL-1α, IL-6, and TNF, were also detected in lung tissues of HPS cases [14]. Intercellular adhesion molecule type 1 (ICAM-1) and vascular cell adhesion molecule type 1 (VCAM-1) provide costimulatory signals that activate T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, expression of viral antigens on the endothelial cell membrane, up regulates CD8+ Cytotoxic T-lymphocytes, enhancing vascular permeability and contributing to Hantavirus syndromes manifestations. Moreover, immune-complex depositions and complement activation are implicated for kidney involvement [14,15].…”
Section: Hantavirus Infection Pathophysiologymentioning
confidence: 99%